Effect of annealing-induced microstructure on the photo-oxidative degradation behavior of isotactic polypropylene. (April 2019) - Liu, Qiang; Liu, Shixiang; Xia, Lei; Hu, Ping; Lv, Yadong; Liu, Junjie; Chen, Zhiquan; Huang, Yajiang; Li, Guangxian
Abstract: Although a great deal of work has been dedicated to revealing the annealing-induced structure and mechanical changes in isotactic polypropylene (iPP), its effect on the photo-degradation behavior is seldom investigated so far. In this work, the correlation between microstructure induced by annealing in vacuum and photo-oxidative degradation behavior of iPP is studied. Lamellae thickening and perfection with increasing crystallinity are observed upon increasing annealing temperature. Besides, the formation of looser amorphous phase due to descendant chain segment concentration and decreased mechanical coupling between crystalline and amorphous regions are also corroborated. Annealing under elevated temperatures leads to decreased solubility coefficient of oxygen, improved radical scavenging ability of crystals and inhibited chain scission, which all synergistically contribute to an enhanced resistance to the photo-oxidation of iPP. However, the UV light absorption is not significantly changed by annealing before photo-oxidation. Electron Paramagnetic Resonance (EPR) results suggest that an effective removal of reactive sites by annealing can also be probably ruled out. In addition, EPR confirms that the total free radical concentration of annealed iPP is lower than that of unannealed samples after chain initiation step during photo-oxidation. Highlights: iPP exhibits an enhanced resistance to photo-oxidation after thermal annealing in vacuum. The result is suggested to be related with the multi-level changes in the microstructure of iPP tuned by annealing. Thermal annealing in vacuum is a promising strategy in improving the comprehensive performance of semicrystalline polymers.